2017
DOI: 10.1016/j.jtho.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Intraoperative Nodal Staging during Surgical Resection of NSCLC: Influencing Factors and Its Relationship to Survival

Abstract: This study provides a much-needed benchmark of current thoracic surgical practice in lung cancer in the United Kingdom and important granularity to facilitate changes to improve adequacy of staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
5
10
1
Order By: Relevance
“…A noticeable growth in the number of evaluated parameters was seen from the year 2009, after the UICC recommendation to observe the practice of intraoperative staging in the Wroclaw Thoracic Surgery Centre. A similar upward trend with regard to staging adequacy (following the implementation of IASLC recommendations) is also reported to happen in one of the British centres (9). Creation of recommendations by scientific societies or research groups with regard to intraoperative assessment of lymph nodes is therefore legitimate, as it leads to improvement of N category staging quality.…”
Section: Discussionsupporting
confidence: 53%
“…A noticeable growth in the number of evaluated parameters was seen from the year 2009, after the UICC recommendation to observe the practice of intraoperative staging in the Wroclaw Thoracic Surgery Centre. A similar upward trend with regard to staging adequacy (following the implementation of IASLC recommendations) is also reported to happen in one of the British centres (9). Creation of recommendations by scientific societies or research groups with regard to intraoperative assessment of lymph nodes is therefore legitimate, as it leads to improvement of N category staging quality.…”
Section: Discussionsupporting
confidence: 53%
“…The patients with left-sided resections had significantly higher rate of inadequate LNS (1). The disparity between left and right concerned LN-stations 2, 4, and 7.…”
Section: Lymphadenectomy and Lymphatics Of The Lungsmentioning
confidence: 91%
“…Edwards and coworkers (1) found that adequate LNS increased significantly from 14% in 2011 to 53% in 2014. All lung cancer resections had been performed by five dedicated thoracic surgeons.…”
Section: Impact Of Specialisation and Effect Of Patients' Volume On Tmentioning
confidence: 97%
See 2 more Smart Citations